Heterogeneous production of Cl2 from particulate chloride: Effects of composition and relative humidity. Issue 8 (6th June 2018) - Faxon, Cameron B.; Dhulipala, Surya Venkatesh; Allen, David T.; Hildebrandt Ruiz, Lea
Abstract : Reactions initiated by chlorine atoms can enhance the formation of ozone (O3 ) and secondary organic aerosol (SOA) in the troposphere. Environmental chamber experiments were conducted to quantify heterogeneous Cl2 production from NH4 Cl and NaCl particles exposed to O3 and hydroxyl radicals (OH). Observations are inconsistent with models of Cl2 production resulting solely from surface‐mediated reactions of OH and suggest that O3 plays a significant role. The production of Cl2 increased with relative humidity and decreased in the presence of SOA or nitric oxides (NOx ). Heterogeneous reactive uptake coefficients for the production of Cl2 from O3 on pure NH4 Cl ( γ O 3 ) averaged 1.4 ± 1.0 × 10 −3 . Cl2 production was six times more efficient on NH4 Cl aerosol than on NaCl aerosol. Model calculations under atmospheric conditions suggest this heterogeneous Cl2 production could increase peak daily O3 concentrations by over 10%. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3151–3158, 2018